Representing Birth in Outi Tarkiainen's Midnight Sun Variations (2019): Stasis, Expansion, and Decay as Temporal Processes - Mutschler, Katherine (Université d'Ottawa | University of Ottawa, 2024)
Outi Tarkiainen’s Midnight Sun Variations (2019) for orchestra is a work about the sun being up at night and its associated blurred temporal boundaries, as well as about pregnancy and birth. I argue that musical representations of the growing daylight towards the summer solstice parallel musical representations of a mother’s labour contractions until she gives birth, as well as the mother’s body shrinking to its former self as the days get shorter. The goal of this thesis is to examine how Tarkiainen musically represents the stasis, growing, and shrinking that constitute the narrative of the piece. To do so, I first relate Tarkiainen’s work to representation of pregnancy in Mina Loy’s poem “Parturition.” Drawing on the work of scholars who write on temporal manipulation, such as Victoria Malawey, Edward Pearsall, Olivier Messiaen, and September Russell, I observe how Tarkiainen inhibits harmonic and rhythmical hierarchy to evoke blurred temporal boundaries. I analyze moments of tension and growth towards the climax, by drawing on Malawey’s concepts of emergence and processive growth. I also borrow Malawey’s notion of decay (shrinking) to discuss how the music that follows the work’s climax fades. Overall, I illustrate how Tarkiainen creates a narrative of stasis and expanded temporality under the midnight sun, as her way of linking the body with the growing and shrinking of the days. Midnight Sun Variations (2019) pour orchestre d'Outi Tarkiainen est une œuvre traitant du solstice d’été en Finlande et des limites temporelles floues qui y sont associées, ainsi que de la grossesse et de la naissance. Je soutiens que les représentations musicales de la lumière du jour grandissant vers le solstice d’été sont parallèles aux représentations musicales des contractions du travail d’une mère jusqu’à ce qu’elle accouche, ainsi que du corps de la mère se rétrécissant suite à la naissance à mesure que les jours raccourcissent. Le but de cette thèse est d’examiner comment Tarkiainen représente musicalement la stase, la croissance et le rétrécissement qui constituent le récit de la pièce. Pour ce faire, je relie d’abord l’œuvre de Tarkiainen à la représentation de la grossesse dans le poème « Parturition » de Mina Loy. En m'appuyant sur les travaux de chercheurs qui écrivent sur la manipulation temporelle, tels que Victoria Malawey, Edward Pearsall, Olivier Messiaen et September Russell, j’observe comment Tarkiainen inhibe la hiérarchie harmonique et rythmique pour évoquer les limites temporelles floues. J’analyse les moments de tension et de croissance vers le point culminant en m’appuyant sur les concepts d’émergence (emergence) et de croissance progressive (processive growth) de Malawey. J’emprunte également la notion de désintégration (decay) de Malawey pour expliquer comment la musique qui suit le point culminant de l’œuvre s’estompe. Dans cette thèse, j’illustre comment Tarkiainen crée un récit de stase et de temporalité élargie sous le soleil de minuit, comme sa manière de relier le corps à la croissance et au rétrécissement des jours.
Keywords: music theory; Outi Tarkiainen; Post-tonal; music; orchestral music